(untitled) (Rudarsko-geološko-naftni zbornik, 2023)
Clogging during excavation is one of the common problems in mechanized excavation. Among the influential factors in clogging of the cutter head, we can mention the percentage of fine soil particles (under 200 mesh sieve), soil moisture, and soil type. In this study, to investigate the mechanism of tunnel excavation in the laboratory, a tunnel excavation machine laboratory simulator was designed and built. The features of this device are its horizontal operation, the low rotation speed of the cutter head, continuous contact of the pins with fresh soil during the test, and the continuous injection of additives with a specific injection pressure during the test. The effect of the percentage of fine-grained, soil moisture and the foam injection ratio (FIR) on clogging, energy consumed, and the average wear of cutting tools was studied. The results showed that with an increase in the percentage of fine soil particles from 90 to 100%, the clogging of cutting tools increased by 50%. Also, with an increase of soil moisture from a dry state to moisture content of 5%, clogging of the cutter head is insignificant, and after that, with an increase of moisture from 10 to 25%, clogging is increased by 178%, and the amount of energy consumed in each test is increased by 84%. In addition, by increasing the foam injection ratio from 40 to 60%, clogging decreased by 81% on average, and the wear of cutting tools decreased by 62% on average.